Scan for MARC: princípios sintáticos e semânticos de registros bibliográficos aplicados à conversão de dados analógicos para o formato MARC 21 bibliográfico - Zafalon, Zaira Regina [UNESP] (2012)
The research presents as its central theme the study of the bibliographic record conversion process. The object of study is framed by an understanding of analogic bibliographic record conversion to the Bibliograhpic MARC21 format, based on a syntactic and semantic analysis of records described according to descriptive metadata structure standards and content standards. The thesis in this research is that the syntactic and semantic principles of bibliographic records, defined by description and visualization cataloguing schemes, present in the descriptive metadata structure standards and content standards, determine the bibliographic record conversion process to the MARC21 Bibliographic Format. In the light of this, the purpose of this research is to develop a theoretical study of the syntax and semantics of bibliographic records, grounded in Linguistic theories of Saussure and Hjelmslev, which can underlie analogic bibliographic record conversion to the MARC21 Bibliographic Format using a computational interpreter. To this end, the general aim was to develop a theoretical-conceptual model of the syntax and semantics of bibliographic records, based on saussurean and hjelmslevian linguistic studies of human language manifestations, which can be applicable to a computational interpreter designed for the conversion of bibliographic records to the MARC21 Bibliographic Format. To attain this goal, the following specific objectives were identified, in two groups and related to the theoretical-conceptual model of bibliographic record syntax and semantics and to the conversion process of the records, respectively: to make explicit the relationship between the syntax and semantics of bibliographic records... (Complete abstract click electronic access below)